Analisis Penggunaan Telemedicine Sebagai Pelayanan Kesehatan Pada Masa Pandemi COVID-19 di RS PKU Muhammadiyah Yogyakarta: Analysis of the Use of Telemedicine as a Health Service During the COVID-19 Pandemic at PKU Muhammadiyah Hospital Yogyakarta - Navisoh; Firman, Firman; Utami, Fitriana Putri; Hastuti, Siti Kurnia Widi; Syam, Nur Syarianingsih (Universitas Ahmad Dahlan, 2023)
Background: The COVID-19 pandemic has brought extraordinary changes to healthcare. The government continues to implement policies to prevent the spread of COVID-19, one of which is the recommendation to use telemedicine. Telemedicine is a form of long- distance service using technology as an effort to accelerate increased access and quality of health services. Telemedicine is a new health service innovation at PKU Muhammadiyah Yogyakarta Hospital. Purpose: This study aims to analyze the use of telemedicine as a health service during the COVID-19 pandemic at PKU Muhammadiyah Yogyakarta Hospital. Methods: This research uses a qualitative research method with a case study approach. The research subjects were six informants who were taken through a purposive sampling technique. Data collection was done by means of in-depth interviews. Results: Access to telemedicine starts with socializing the telemedicine program on social media which explains the flow of telemedicine in accordance with the SOP. The quality of telemedicine is considered good with the existence of infrastructure that supports the telemedicine program, although the opportunities for telemedicine development are said to be not maximized because they do not yet have targets to achieve. The purpose of telemedicine is to assist patients in obtaining health services wherethey cannot visit the hospital directly, the implementation of the telemedicine program has been able to provide quality and satisfying services despite obstacles from staff and patients. Conclusion: The use of telemedicine at PKU Muhammadiyah Yogyakarta Hospital is quite good starting from access to services, quality of telemedicine and user satisfaction. But there are still obstacles, namely the lack of human resources, financial unit officers who do not immediately provide confirmation to patients, to problems with patients. So it is hoped that PKU Muhammadiyah YogyakartaHospital can carry out internal monitoring and evaluation of the telemedicine program.